The system functions of direct democracy - a ranking of 103 countries in the world - Hornig, Eike-Christian; Frommelt, Christian (Frontiers in Political Science, 2024)
We introduce a new framework of the functions of direct democracy within a democratic political system. These are: (1) channeling political input into the decision-making arenas by circumventing organized interests (input function), (2) channeling political issues out of the representative decision-making system (exit function), and (3) producing decisions about political questions (decision function). Based on the analysis of 277 instruments of direct democracy on the national level in 103 countries around the world, we find that the input and exit functions are rather unbalanced in their dynamics. The exit function shows a tendency to strengthen the concentration of power, whereas the input function rarely allows for access to both decision-making arenas. However, once issues reach the referendum, the impact is often strong, and only a small minority of states conduct referendums without any formal consequences. Beyond these results, the presented approach allows to start long-time observations of the state of direct democracy in democratic systems.